Four Coptic Letters from Thebes - Khalil, Ahmed T. A. (Zeitschrift für ägyptische Sprache und Altertumskunde, 2023)
The Coptic correspondences of Thebes are not only characterized by the variety of topics but also by some formulae that have become a distinctive feature of this region. The aim of the present paper is to publish four Coptic letters on ostraka; they are now kept in the Abou El-Goud storage magazine in Luxor. Although there is no information on their provenance, they are certainly written in the Theban area.